Speech Acts Analysis in the Film Atonement (2007) - Rasya Regina Shafa; Otong Setiawan Djuharie (Syntax Idea, 2026)
Miscommunication about the meaning of words in some situation is a common problen that we faced in a daily life by both speakers and hearers. It was interesting how we can find out about language functions in human interaction, taking into the context that affects communication as well. Then, this research aims to identify the types of speech acts in the film of Atonement (2007). This study employed a qualitative descriptive research because the analysis focused on interpreting utterances based on their character’s meaning and function in context. Utilizing George Yule’s theory about speech act, the findings reveal four of the five types of speech acts which are representatives, directives, expressives, and commissives. The dominant category of this finding reached 88 out of a total of 202 types of speech (43%). The speech acts in the film serve various purposes, incluiding reporting information, stating the truth, expressing emotion, making request, refusing unwanted propotions, etc. This study presents numerous meaning and function of utterances that language serves by the characters in the film Atonement (2007).